Capillary imbibition in cement-based materials with time-dependent permeability. (October 2019) - Hall, Christopher
Abstract: Models of capillary imbibition (or absorption) generally assume that materials remain stable during wetting, and that transport properties do not change. This is also assumed in standard tests to measure the sorptivity of porous construction materials. Anomalies in the water imbibition behaviour of cement-based materials are occasionally reported. In some cases, these may arise from the alteration of materials on contact with water. The property most sensitive to wetting is the permeability. Here, a Sharp Front imbibition model is developed that incorporates a time-varying permeability. The concept of a contact time is introduced to describe the duration of contact between material and water at any location. Imbibition kinetics shows a crossover from early-time to late-time behaviour. During crossover, there is a deviation from standard (time) 1/2 behaviour, as the permeability decrease retards the advance of the wet front. Published experimental data are well represented by the model.